Establishing an ECMO program in a developing country: challenges and lessons learned. (September 2019) - Assy, Jana; Skouri, Hadi; Charafeddine, Lama; Majdalani, Marianne; Younes, Khaled; Bulbul, Ziad; Sfeir, Pierre; Bourgi, Jamil; Hallal, Ali; Rifai, Khaled; Zaatari, Rafika; Bitar, Fadi; et al.
Aim: The ECMO (extracorporeal membrane oxygenation) Program at the American University of Beirut Medical Center was established in November 2015 as the first program serving adult and pediatric population in a low-resource setting. The aim of the study is to describe the challenges faced during the establishment of the program and factors leading to its success. Methods: The program establishment is described. The preparation phase, included the strategic, financial, and clinical planning by administration, nursing, and a multidisciplinary team of physicians. The training and education phase included all the involved nurses, perfusionists, and physicians. Concerns were heard from various stakeholders, and the challenges were analyzed and discussed. Results: The preparation committee chose the adequate equipment, responded to the concerns, defined roles and responsibilities through credentialing and privileging, wrote policies and protocols, and established a strategy to decide for the ECMO indication. Selected team of nurses, physicians, and perfusionists are identified and trained locally, and abroad. A full-time ECMO physician was recruited to launch the program. Twelve patients (6 adults, 3 children, and 3 neonates) were supported by ECMO, for cardiac and respiratory indications. Eleven patients were supported by veno-arterial ECMO, and 1 patient (a neonate) with veno-venous ECMO. Overall, 75% survived to decannulation and 41% survived to discharge. Conclusion: With limited human and financial resources, new ECMO centers need to carefully establish selection criteria that may differ from those used in developed countries. Indications should be discussed on a case by case basis, taking into account clinical, social, and financial issues. This experience might help other institutions in developing countries to build their own program despite financial and human limitations.